2013
DOI: 10.1242/jcs.128280
|View full text |Cite
|
Sign up to set email alerts
|

A functional siRNA screen identifies genes modulating angiotensin II-mediated EGFR transactivation

Abstract: SummaryThe angiotensin type 1 receptor (AT 1 R) transactivates the epidermal growth factor receptor (EGFR) to mediate cellular growth, however, the molecular mechanisms involved have not yet been resolved. To address this, we performed a functional siRNA screen of the human kinome in human mammary epithelial cells that demonstrate a robust AT 1 R-EGFR transactivation. We identified a suite of genes encoding proteins that both positively and negatively regulate AT 1 R-EGFR transactivation. Many candidates are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 75 publications
1
41
0
Order By: Relevance
“…Angiotensin II activates the angiotensin type 1 receptor (AT1R), which then transactivates the epidermal growth factor receptor (EGFR) to mediate cellular growth. Knockdown of Bmx was shown to attenuate tyrosine phosphorylation of the EGFR by angiotensin II stimulation in mammary epithelial cells, but Bmx did not have an effect on direct stimulation of the EGFR with EGF, indicating that Bmx functions between the activated AT1R and EGFR (21). Bmx also induces the tyrosine phosphorylation and DNA binding activity of STAT1, STAT3, and STAT5 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II activates the angiotensin type 1 receptor (AT1R), which then transactivates the epidermal growth factor receptor (EGFR) to mediate cellular growth. Knockdown of Bmx was shown to attenuate tyrosine phosphorylation of the EGFR by angiotensin II stimulation in mammary epithelial cells, but Bmx did not have an effect on direct stimulation of the EGFR with EGF, indicating that Bmx functions between the activated AT1R and EGFR (21). Bmx also induces the tyrosine phosphorylation and DNA binding activity of STAT1, STAT3, and STAT5 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Zhang et al (2015) showed that the cardioprotective  opioid receptor transactivates the EGFR via PKC dependent ligand shedding, with -arrestin2 recruited to the distal EGFR (not the  opioid receptor). Finally, a recent functional siRNA screen in human epithelial cells has identified novel mediators of EGFR transactivation, including TRIO, BMX and CHKA (George et al, 2013b). Their knockdown impairs EGFR phosphorylation in response to GPCR agonism, but not direct activation with EGF, locating the proteins between the GPCR and EGFR.…”
Section: Mechanisms Of Egfr Transactivationmentioning
confidence: 99%
“…Individual down regulation of TRIO, BMX or CHKA attenuated the activation of EGFR by Ang II, but not by the EGFR agonist EGF, suggesting that these factors are located upstream of EGFR and required for EGFR transactivation (George et al, 2013). These studies suggested that the pathway for GPCR to transactivate EGFR is much more complicated than that previously proposed.…”
Section: Potential Mechanisms For Erbb1 Transactivation By Ang Ii: Thmentioning
confidence: 81%
“…Indeed, our group has recently used functional genomics to perform a siRNA screen of AT 1 R-ErbB1 transactivation in a mammary epithelial cell line, and have identified a number of novel molecules involved in this process (George et al, 2013). It is also important to recognize the difficulties in characterizing systems that involve multiple molecular participants, and thus may have a high degree of redundancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation